DIGITAL TRANSFORMATION AND BICHRONOUS LEARNING DURING WAR: A PRACTICAL EXAMPLE OF PREPARING FUTURE NANOENGINEERS - Suchikova, Yana; Kovachov, Serhii; Popova , Anastasiia; Bohdanov , Ihor (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article proposes a strategy for emergency response and reformatting of existing training courses and training programs for future nanoengineers to a distance format using synchronous and asynchronous learning tools. Using the example of the Berdyansk State Pedagogical University, the authors of the article demonstrate a step-by-step plan for training nanoengineers during the war, which includes the development of task packages for processing large data of research results, the use of a large package of software tools for data processing and visualization, the inclusion of artificial intelligence technologies in the educational and research training process specialists.